Direct Corrective Feedback in Improving Students’ Writing Ability - M Syamsir (Universitas Cokroaminoto Palopo, 2016)
The objective of the research was to find out whether or not the use of direct corrective feedback could improve the students’ writing ability to the fourth semester students of Sekolah Tinggi Ilmu Keperawatan (STIK) Stella Maris Makassar. The researcher applied quasi-experimental method using non-equivalent control class design. The Population of this research was the fourth semester students of Sekolah Tinggi Ilmu Keperawatan (STIK) Stella Maris Makassar in academic year 2013/2014. The sample was class A and class B, which consists of 80 students. This research used cluster random sampling. The researcher chose two classes of the fourth semester students of Sekolah Tinggi Ilmu Keperawatan (STIK) Stella Maris Makassar randomly, as the experimental class and the control class. The two classes were given treatment. The experimental class was treated by direct corrective feedback while the control class was taught with usual interaction feedback. The data were collected through writing test. The result of the data analysis showed that there was significant difference between the students’ score who were taught by using direct feedback and only with usual interaction feedback. It is proved by the mean score of the experimental class is higher than control class in the posttest. Moreover, the result of test of significant analysis indicates that the use of corrective direct feedback significantly improve the students’ writing ability. Based on the result, it could be concluded that the use direct of corrective feedback improved the students’ writing ability of the fourth semester students of Sekolah Tinggi Ilmu Keperawatan (STIK) Stella Maris Makassar in academic year 2013/2014.